Relative condition factor and gonado-somatic index in Sillago sihama (Forskal) - Reddy, C R; Neelakantan, B (Indian Journal of Fisheries, 2011)
The weight of a fish varies with the cubeof its length. Variations from the expectedweight from the length of individual fishes orgroup of fishes are detected by analysing thelength-weight relationship. The condition factoris given by the formula K = 100 W/L 3where' K' represents the condition factor. 'W'the weight of fish and 'L' the len~rth of fish.This tormula is based on comparison with anideal fish where the cube relationship holdsgood. Le Cren (1951) proposed the relativecondition factor, 'Kn', in preference to conditionfactor as the latter is highly influenced bymany environmental and biological factors.